Intraoperative Tracheal Obstruction Management among Patients with Anterior Mediastinal Masses - H. Kafrouni; Joelle Saroufim; Myriam Abdel Massih (Case Reports in Medicine)
Background. Patients suffering from undiagnosed obstruction of the central airways: the trachea and main stem bronchi are at increased risk for perioperative and postoperative complications, especially if general anesthesia is performed. Case Description. This report discusses a 30-year-old asymptomatic Caucasian female who faced recurrent distal airway collapse during mediastinoscopy for biopsy of an anterior mediastinal mass, which led to the inability to extubate her. This case examines the necessity of a thorough preoperative assessment especially in patients with undiagnosed tracheal obstruction and a precise coordination between anesthesiologist and surgeon in being able to perform a safe and smooth anesthesia, in order to avoid life-threatening complications and to reduce further morbidity. Methods. The scope of this case report is restricted to publications in all surgical and anesthesiological specialties among adult patient population. Main search key words were as follows: “tracheal obstruction,” “general anesthesia,” “mediastinum,” and “tumors” Results. The literature supports an increased perioperative risk of airway obstruction with the use of general anesthesia in patients with anterior mediastinal masses. This case report suggests a perioperative anesthetic management modality for patients presenting with anterior mediastinal masses and who are at high risk of cardiovascular compression and tracheal obstruction. Thus, it is highly important to note that evidence-based recommendations are not available in the literature. Conclusions. This case report suggests perioperative management modalities performed by anesthesiologists in order to minimize the risk of airway obstruction among patients having anterior mediastinal masses and shed the lights on the importance of proper anesthetic and surgical planning in order to prevent intraoperative complications and improve the quality of healthcare provided to patients presenting critical cases.